A nucleic acid amplification test‐based strategy does not help inform return to work for healthcare workers with COVID‐19. Issue 5 (26th May 2022) - Hijano, Diego R.; Hoffman, James M.; Webby, Richard J.; Tang, Li; Hakim, Hana; Hayden, Randall T.; Gaur, Aditya H.
Abstract: Objective: The objective of this study is to assess the utility of a nucleic acid amplification test‐based approach to shorten isolation of healthcare workers (HCWs) with COVID‐19 in the setting of the highly transmissible omicron variant. Methods: Between December 24, 2021, and January 5, 2022, HCWs who tested positive for SARS‐CoV‐2 were retested with PCR at least 5 days since onset of symptoms. Results: Forty‐six sequential fully COVID‐19 vaccinated HCWs who had tested positive for SARS‐CoV‐2 underwent follow‐up testing. All the samples were confirmed as omicron variants and only four (8.7%) were negative in the follow‐up test performed at a median of 6 (range 5–12) since onset of symptoms. Conclusions: Implementation of a test‐based strategy is logistically challenging, increases costs, and did not lead to shorter isolation in our institution.